Penerapan Kebijakan Anti-Dumping WTO sebagai Bentuk Tindakan Proteksi - Rizmawati Darmawan; Irawati (Jurnal Riset Ilmu Hukum, 2021)
Abstract. Anti-dumping policy settings are clearly stated in the WTO - Agreement on Implementation of Article VI of The General Agreement on Tariffs and Trade 1994. The application of anti-dumping import duties as a protective measure is carried out by countries in order to protect their country’s economy. This policy can be applied when a country meets several criteria in the classification of proven dumping as stated in the Article VI GATT 1994. Therefore, this study aims to find out the implementation and provisions of anti-dumping policy based on Agreement on Implementation of Article VI of The General Agreement on Tariffs and Trade 1994. This research method uses normative juridical approach with two concepts of comparison approach and case approach. By using descriptive analysis research specifications and data collection techniques through literature study. The results of this study concluded that based on Article VI anti-dumping policy can be enforced if at the time of the investigation process indicated the existence of dumping, the existence of material losses experienced in the domestic industry that produces similar goods, and the existence of a causal relationship between dumping and damage Abstrak. Pengaturan kebijakan anti-dumping secara jelas tercantum dalam WTO - Agreement on Implementation of Article VI of The General Agreement on Tariffs and Trade 1994. Pemberlakuan bea masuk anti-dumping sebagai tindakan proteksi dilakukan oleh negara-negara guna melindungi perekonomian negaranya. Kebijakan ini dapat diberlakukan ketika suatu negara memenuhi beberapa kriteria dalam klasifikasi terbukti adanya dumping yang tercantum dalam Article VI GATT 1994. Oleh karena itu penelitian ini bertujuan untuk mengetahui implemtasi dan ketentuan kebijakan anti-dumping berdasarkan Agreement on Implementation of Article VI of The General Agreement on Tariffs and Trade 1994. Metode penelitian ini menggunakan pendekatan yuridis normatif dengan dua konsep pendekatan perbandingan dan pendekatan kasus. Menggunakan spesifikasi penelitian deskriptif analisis dan teknik pengumpulan data melalui studi kepustakaan. Hasil penelitian ini menyimpulkan bahwa berdasarkan Article VI kebijakan anti-dumping dapat diberlakukan apabila pada saat proses investigasi terindikasi adanya dumping, adanya kerugian material yang dialami pada industri dalam negeri yang memproduksi barang sejenis, dan adanya hubungan sebab akibat antara dumping dan kerusakan.